6(p-5)-(4p+9)=25

Simple and best practice solution for 6(p-5)-(4p+9)=25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(p-5)-(4p+9)=25 equation:


Simplifying
6(p + -5) + -1(4p + 9) = 25

Reorder the terms:
6(-5 + p) + -1(4p + 9) = 25
(-5 * 6 + p * 6) + -1(4p + 9) = 25
(-30 + 6p) + -1(4p + 9) = 25

Reorder the terms:
-30 + 6p + -1(9 + 4p) = 25
-30 + 6p + (9 * -1 + 4p * -1) = 25
-30 + 6p + (-9 + -4p) = 25

Reorder the terms:
-30 + -9 + 6p + -4p = 25

Combine like terms: -30 + -9 = -39
-39 + 6p + -4p = 25

Combine like terms: 6p + -4p = 2p
-39 + 2p = 25

Solving
-39 + 2p = 25

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '39' to each side of the equation.
-39 + 39 + 2p = 25 + 39

Combine like terms: -39 + 39 = 0
0 + 2p = 25 + 39
2p = 25 + 39

Combine like terms: 25 + 39 = 64
2p = 64

Divide each side by '2'.
p = 32

Simplifying
p = 32

See similar equations:

| 11a+18b+6C+4C-4B-2A= | | 8x+17=25 | | 15-(y+6)=16 | | 2(4a+2)-3(2a-4)= | | -3(x-5)+2(4x-8)=12 | | 2x^2+3x=200 | | 0.5x^2+3x-36=0 | | 2xy-5yx+7= | | 180(3.14)=2(3.14)*10 | | 28=4v-8 | | 60+20x=96+11x | | 7(8)-3(-8)=5 | | 9z-90=-4z-10 | | x+3=-3+x-2+8 | | y=-3(8)+2 | | y=-3(8)x+2 | | y=-3(0)x+2 | | 2(8s+2)-6s=2(5s+4)-13 | | 7x+17=4x+1 | | 12(3x+3)-5(2x-3)=6x-49 | | 0.55x+0.05(10-x)=0.10(-25) | | 9x+10-6x=6x+40 | | -2(x-8)=4(x+1) | | 10x+7+5x=7x+31 | | (t+9)+(4t-15)= | | 17x+4=10-45 | | 12y+8=5y-5 | | 5(-4)-4y=20 | | (Gx)=6x^2-224x+4941 | | solvex^3-2x-1.5=0 | | x^3-2x-1.5=0 | | 172-6x=5x+18# |

Equations solver categories